Risk Factors of Retained Placenta after Vaginal Delivery in Pathum Thani Hospital - Bhuttarechval, Vivat (Journal of Health Science of Thailand, 2019)
For most parturients, the third stage of labor was short and uneventful. With vaginal delivery,a retained placenta was usually diagnosed when the duration of the third stage exceeded 30 minutes. Although controversial, surgical intervention, including manual removal of the placenta has been advocated. Previous studies have reported many risk factors of retained placenta. The objective of this study was to identify risk factors associated with retained placenta after vaginal delivery. Thus, case control study was designed. The study was conducted during the period 1 January 2005-30 June 2006. Medical records of 141 pregnant women whose gestational age ≥ 28 weeks were reviewed.Studied group comprised 47 women with retained placenta after vaginal delivery and controlled group comprised 94 women with spontaneous placental delivery. Associated risk factors were examined. Mean ± standard deviation and Student T test analysis were used for analysis of data with statistical significance (p < 0.05). The result came out in such a way that study group was significantly different from control group in that they have more than controls of a previous history of uterine curettage (36.17% vs 14.89% respectively, p=0.004) and premature rupture of membranes (31.9% vs 17% respectively, p=0.044) and lower placental weight (524.89±59.12 vs 580.11±46.85 respectively, p=.007) and parity (p=0.006). Between the two groups, there were no differences in maternal age, gestational age,previous retained placenta, onset of labor or oxytocin usage. In conclusion, the study confirms some previous observation risk factors which shows that there should be awareness with regard to pregnantwomen with such risk factors. A properly conducted delivery can reduce the incidence of retained placenta and if it occurs, timely appropriate treatment can save lives.